2020
DOI: 10.1002/jbt.22452
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MST1P2/miR‐133b axis affects the chemoresistance of bladder cancer to cisplatin‐based therapy via Sirt1/p53 signaling

Abstract: Although bladder cancer is commonly chemosensitive to standard first-line therapy, the acquisition of the resistance to cisplatin (DDP)-based therapeutic regimens remains a huge challenge. Noncoding RNAs (ncRNAs), including long noncoding RNAs (lncRNAs) and microRNAs, have been reported to play a critical role in cancer resistance to DDP.Here, we attempted to provide a novel mechanism by which the resistance of bladder cancer to DDP treatment could be modulated from the perspective of ncRNA regulation.We demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Histological epithelial neoplasms account for 95% of this disease, among which more than 90% are transitional epithelial cell carcinomas. 24,25 The EJ cell line is derived from malignant BC and is progressing to the muscle layer of the bladder wall, in contrast to cell lines derived from non-muscle-infiltrating BC, an early form of BC. At present, different treatment methods are available for BC depending on the pathological stage and grade.…”
Section: Discussionmentioning
confidence: 99%
“…Histological epithelial neoplasms account for 95% of this disease, among which more than 90% are transitional epithelial cell carcinomas. 24,25 The EJ cell line is derived from malignant BC and is progressing to the muscle layer of the bladder wall, in contrast to cell lines derived from non-muscle-infiltrating BC, an early form of BC. At present, different treatment methods are available for BC depending on the pathological stage and grade.…”
Section: Discussionmentioning
confidence: 99%
“…MST1P2 was reported to be significantly upregulated in cisplatin-resistant BC cell lines where it serves as a ceRNA. Indeed, MST1P2 sponges miR-133b, where the expression level was downregulated in the same cell lines [27]. Interestingly, the participation of miR-133b in the regulation of chemoresistance was already described in ovarian cancer [118], colorectal cancer [119], and osteosarcoma [120].…”
Section: Mst1p2mentioning
confidence: 93%
“…Interestingly, the participation of miR-133b in the regulation of chemoresistance was already described in ovarian cancer [118], colorectal cancer [119], and osteosarcoma [120]. Among direct targets of this short RNA is oncogene Sirt1 (Sirtuin 1) which was proposed as a possible effector of MST1P2/miR-133b mediated drug resistance [27]. Sirt1 overexpression can inactivate p53, which results in a low response of cancer cells with unmutated p53 to DNA-damaging chemotherapeutics [121] and thus inhibition of cancer cells apoptosis (Figure 2).…”
Section: Mst1p2mentioning
confidence: 99%
“…MiR-133b directly suppressed the SIRT1 expression. MST1P2/miR-133b axis had an important role in cisplatin-resistance of BCa through SIRT1/p53 pathway [17]. It has been shown that there was overexpression of HIF1A-AS2 in tissues and cell lines of BCa following the cisplatin treatment which makes bladder tumor cells resistance to cisplatin-triggered cell death.…”
Section: Long Non Coding Rnasmentioning
confidence: 99%